Kajian Neuroscience dalam Pengembangan Ilmu Sekolah Dasar - Rizky Amelia; Kus Eddy Sartono; Chairil Faif Pasani (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2020)
This article aims to explain the implementation of neuroscience studies in the development of science in elementary schools. The method of writing this article is literature study by exploring various scientific papers related to this topic. The results of the author's study convey that the structure of the nervous system underlies human action, both aspects of cognition, affection, and psychomotor. Implementation of the results of neuroscience studies in the development of science in elementary schools involves neuroscience, cognitive neuroscience, psychology, educational theory, and learning practices. The concept of learning in a neuroscience perspective is learning that empowers the brain's abilities by creating a learning environment that is challenging, fun, meaningful, and encourages students to be active. Thus, educational neuroscience is an important future educational model for primary school teachers to know.